x = -√7 atau x = √7
Penjelasan dengan langkah-langkah:
(x-1) (x+3) = 2x+4
x² + 3x - x - 3 = 2x + 4
x² + 2x - 3 = 2x + 4
x² + 2x - 3 - 2x - 4 = 0
x² - 7 = 0
x² = 7
x = ±√7
(x - 1)(x + 3) = 2x + 4
x(x + 3) - 1(x + 3) = 2x + 4
x² + 3x - 1x - 3 = 2x + 4
x² + 2x - 2x - 3 - 4 = 0
HP{-√7, √7}
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
x = -√7 atau x = √7
Penjelasan dengan langkah-langkah:
(x-1) (x+3) = 2x+4
x² + 3x - x - 3 = 2x + 4
x² + 2x - 3 = 2x + 4
x² + 2x - 3 - 2x - 4 = 0
x² - 7 = 0
x² = 7
x = ±√7
x = -√7 atau x = √7
Penjelasan dengan langkah-langkah:
(x - 1)(x + 3) = 2x + 4
x(x + 3) - 1(x + 3) = 2x + 4
x² + 3x - 1x - 3 = 2x + 4
x² + 2x - 3 = 2x + 4
x² + 2x - 3 - 2x - 4 = 0
x² + 2x - 2x - 3 - 4 = 0
x² - 7 = 0
x = ±√7
x = -√7 atau x = √7
HP{-√7, √7}